Chemosensors : principles, strategies, and applications - Wang, Binghe; Anslyn, Eric V., 1960- (Hoboken, N.J. : Wiley, 2011)
'This book offers a general overview of chemosensors and their applications, including topics like molecular recognition, detection methods, design strategies, and important biological issues'--
Includes bibliographical references and index.
Keywords: Biosensors; Molecular recognition; Chemical detectors; SCIENCE / Chemistry / Organic $2 bisacsh; Biosensor; Chemischer Sensor; Molekulare Erkennung; Biosensing Techniques; Models, Chemical; Molecular structure